The tale of Jemima Puddle-Duck - Potter, Beatrix, 1866-1943. (Harmondsworth, Middlesex, England ; New York, N.Y., U.S.A. : F. Warne, 1987)
Three dogs rescue a foolish duck when she decides to hatch her eggs in a fox's house.
Elem. School Library Collection
Reference and Research Book News
School Library Media Quarterly (A.A.A.L.)
3.9
K-3
AD770L
Keywords: Ducks; Ducks; Fiction; Fiction